Sales management for dummies - Bellah, Butch (Tantor Audio, 2019)
Guide your sales force to its fullest potential With a proven sales management and execution process, Sales Management For Dummies aids organizations and individuals in reaching the highest levels of success. Although selling products or services is a central part of any sales job, there's much more to it. With this fun and accessible guide, you'll go beyond the basics of sales to learn how to anticipate clients' needs, develop psychologist-like insight, and so much more. Because few people go to school to earn degrees in selling, sales talent is developed in the field. Unfortunately, most training efforts fail to reach their objectives, in large part because of the absence of any kind of reinforcement or coaching. This book is your one-stop guide to managing an existing or start-up sales force to succeed in every area of sales-from prospecting to closing. If you're one of the millions of salespeople or sales managers worldwide looking for a fast, easy, and effective way to get the most out of your sales force, the tried-and-true guidance presented in this book sets you up for success.
Online resource; title from title details screen (OverDrive, viewed November 7, 2019)
Keywords: Sales management; Ventes; Gestion; BUSINESS & ECONOMICS; Sales & Selling; Management; Downloadable audio books; Audiobooks; Livres audio